Pengaruh Lingkungan Kerja, Kesejahteraan Kerja, Keterampilan Kerja Dan Pembagian Kerja Terhadap Prestasi Kerja Pegawai Dinas Lingkungan Hidup Kabupaten Empat Lawang - Taufik, M; Aprini, Nisma; Yulanda, Delvina (Universitas Dehasen Bengkulu, 2025)
The author's research aimed to determine and analyze the influence of the work environment, work welfare, work skills, and division of labor, both individually and collectively, on the work performance of employees at the Environmental Service of Empat Lawang Regency. The research method used in this study was quantitative, using a questionnaire distributed to respondents. Data quality was tested using validity, reliability, and normality tests. The analysis used descriptive and inferential analyses using statistical calculations using multiple regression formulas, partial simultaneous tests, and coefficients of determination. The results showed that the work environment significantly influenced the work performance of employees at the Environmental Service of Empat Lawang Regency. Work welfare significantly influenced the work performance of employees at the Environmental Service of Empat Lawang Regency. Work skills significantly influenced the work performance of employees at the Environmental Service of Empat Lawang Regency. The division of labor significantly influenced the work performance of employees at the Environmental Service of Empat Lawang Regency. The work environment, work welfare, work skills, and division of labor significantly influenced the work performance of employees at the Environmental Service of Empat Lawang Regency.